2014
DOI: 10.5487/tr.2014.30.4.267
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Lead on Repetitive Behavior and Dopamine Metabolism in a Mouse Model of Iron Overload

Abstract: Exposures to lead (Pb) are associated with neurological problems including psychiatric disorders and impaired learning and memory. Pb can be absorbed by iron transporters, which are up-regulated in hereditary hemochromatosis, an iron overload disorder in which increased iron deposition in various parenchymal organs promote metal-induced oxidative damage. While dysfunction in HFE (High Fe) gene is the major cause of hemochromatosis, the transport and toxicity of Pb in Hfe-related hemochromatosis are largely unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
1
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 30 publications
1
34
1
5
Order By: Relevance
“…In the experiments where mice were exposed to Pb for 30 days, for example, the average value in the control is 0.81 mg/g (810 ng/g). This is much higher than most researches concerning Pb-exposed mice, where brain Pb concentration in the control is either below 0.1 mg/g or undetectable Ferlemi et al, 2014;Chang et al, 2014;Ivanova et al, 2016;Li et al, 2016). The value 810 ng/g of control in this study is even higher than that of a high level Pb-exposed group in other studies (Ferlemi et al, 2014;Li et al, , 2016Ivanova et al, 2016).…”
Section: The Levels Of Toxic Metals In Controls Are Extremely Highcontrasting
confidence: 68%
“…In the experiments where mice were exposed to Pb for 30 days, for example, the average value in the control is 0.81 mg/g (810 ng/g). This is much higher than most researches concerning Pb-exposed mice, where brain Pb concentration in the control is either below 0.1 mg/g or undetectable Ferlemi et al, 2014;Chang et al, 2014;Ivanova et al, 2016;Li et al, 2016). The value 810 ng/g of control in this study is even higher than that of a high level Pb-exposed group in other studies (Ferlemi et al, 2014;Li et al, , 2016Ivanova et al, 2016).…”
Section: The Levels Of Toxic Metals In Controls Are Extremely Highcontrasting
confidence: 68%
“…Furthermore, the cytotoxicity of soluble metals resulting from intracellular dissolution of metal NPs should be rigorously examined. Numerous studies have demonstrated biochemical alterations and behavioural dysfunction in animals and humans caused by exposure to various metals (Chang et al, 2014;Kim, 2015a, 2015b;Menon et al, 2016). Measuring the soluble metal concentrations of NP-exposed cells and cell culture media would provide important information about the potential effect of NP dissolution on metal toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Immunoreactivity was detected using ECL Amersham (GE Healthcare, Little Chalfont, Buckinghamshire, UK). The resulting protein bands were visualized by ChemiDoc XRS (Bio-Rad, Hercules, CA, USA) and their intensities were quantitated using Quantity One software (version 4.6.6; Bio-Rad) (Chang et al, 2014).…”
Section: Western Blot Analysismentioning
confidence: 99%